Design of Mechanical Coffee Pulper Equipment - Johanes Mikael Simanulang; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The constraint of capacity of semi mechanical coffee skin pulper is one of the obstacles to increase the coffee production. To overcome this, we need a motor-driven mechanical coffee skin pulper. The research was conducted with the study of literature and observations of semi mechanical coffee skin pulper. Then mechanical coffee skin pulper was designed. Effective capacity was 117.39 kg/h or 821.73 kg/day. This was greater than human driven semi mechanical coffee skin pulper. Basic costs to be spent in coffee pulping with this device was Rp. 85.159 /kg in the 1st year, Rp. 76.139 /kg in the 2nd year, Rp. 73.137 /kg in the 3th year, Rp. 71.638 /kg in the 4th year, and Rp. 70.741 /kg in the 5th year. This equipment will reach break-even point if it has been pulping coffee at 15104.499 kg/year. Net present value of these tools with 6% interest rate was Rp. 72,378,030.96 which means that the business was feasible to run. Internal rate of return on these instruments was 42.64%. Keywords : equipment design, mechanical pulper, coffee pulp